Infected Completely Isolated Enteric Duplication Cyst Management with Percutaneous Drainage and Surgical Excision after Retreat of Infection: A Case Report. (7th February 2013) - Kyriakos, Neofytou; Andreas, Chysochos; Elena, Sammouti; Charalampos, Andreou; Chrisanthos, Georgiou
Abstract : Duplication cysts (DCs) of alimentary tract are rare congenital malformations. They are firmly attached to the wall of the gastrointestinal tract and they are supplied by surrounding mesenteric blood vessels. More than 80% of cases occur before the age of two years and only a minority of cases present in adulthood. "Completely isolated duplication" of the alimentary tract is an extremely rare variety of gastrointestinal duplications. They have gastrointestinal epithelial and wall characteristics without an anatomic association with the alimentary tract. Their main characteristic is that they have their own blood supply. A 20-year-old male was admitted to our department with symptoms persisting for a period of one week prior to admission, which included abdominal pain, fever, and a palpable abdominal mass. CT revealed an unexplained intraperitoneal abscess. This case represents a rare clinical example of infected isolated duplication cyst managed with percutaneous drainage and surgical excision of the cyst 3 weeks later. To the best of our knowledge, this is the first reported case to use this approach.